Case Report: Asymptomatic SARS-COV2 infection triggering recurrent Takotsubo syndrome - Dall’Ara, Gianni; Compagnone, Miriam; Carletti, Roberto; Piciucchi, Sara; Gardini, Elisa; Galvani, Marcello (Frontiers in Cardiovascular Medicine, 2024)
Takotsubo syndrome (TTS) is a rare disease mimicking acute coronary syndrome, often triggered by physical or emotional stress, and characterized by transient left ventricular dysfunction. Recurrences are described in about 5% of cases and may have different clinical and imaging patterns. In the present report, SARS-COV-2 infection, even in the absence of symptoms and overt emotional stress, seems correlated with recurrence of TTS, due to the absence of other recognized triggers. The hypothesis is that in predisposed patients, events like catecholamine-induced myocyte injury, direct viral damage, cytokine storm, immune-mediated damage, and procoagulant state, all possibly induced by the infection, may elicit endothelial dysfunction as substrate for TTS onset.